ChemInform Abstract: Synthesis and Electrochemical Properties of Spinel Li(Li0.05Cu0.05Mn1.90)O4 by a Flameless Combustion Method. Issue 19 (April 2016) - Hao, Jiabin; Bai, Hongli; Liu, Jintao; Yang, Fangli; Li, Qiling; Su, Changwei; Guo, Junming
Abstract: The title material is prepared by a flameless combustion method from a stoichiometric mixture of LiNO3, LiOAc, Mn(NO3 )2, Mn(OAc)2, and Cu(NO3 )2 (500 °C, 3 h) followed by calcination (700 °C, 6 h).